2012
DOI: 10.1088/0031-8949/86/05/055401
|View full text |Cite
|
Sign up to set email alerts
|

Properties of nano-islands formation in nonequilibrium reaction–diffusion systems with memory effects

Abstract: We study dynamics of pattern formation in systems belonging to class of reaction-Cattaneo models including persistent diffusion (memory effects of the diffusion flux). It was shown that due to the memory effects pattern seletion process are realized. We have found that oscillatory behavior of the radius of the adsorbate islands is governed by finite propagation speed. It is shown that stabilization of nano-patterns in such models is possible only by nonequilibrium chemical reactions. Oscillatory dynamics of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 41 publications
0
26
0
8
Order By: Relevance
“…at τ ≠ 0) we have discussed in details in our previous study (see Ref. [39]). It was shown that due to finite propagation speed v = L d /τ related to nonzero τ pattern selection processes can be observed.…”
Section: Modelmentioning
confidence: 92%
“…at τ ≠ 0) we have discussed in details in our previous study (see Ref. [39]). It was shown that due to finite propagation speed v = L d /τ related to nonzero τ pattern selection processes can be observed.…”
Section: Modelmentioning
confidence: 92%
“…В роботі [39] для опису процесів формування структур адсорбату при конденсації з газової фази автори використовували модель реа-кційно-дифузійного типу з урахуванням нерівноважних хемічних реакцій, що відповідають утворенню стійких димерів. Було пока-зано, що за умов малого але кінцевого часу релаксації потоку адсор-бату в системі реалізується коливальна поведінка статистичних моментів та лінійного розміру острова адсорбату.…”
Section: вступunclassified
“…У такому разі всю поверхню розіб'ємо на комірки, в кожній з яких концентрація адсорбату x(r,t) набуває значень в інтервалі [0, 1]; t -часова змінна, r -просторова координата. Згідно з припущеннями та результатами попередніх досліджень, будемо враховувати на-ступні процеси, що протікають при конденсації з газової фази: 1) адсорбція -частинки одного сорту (атоми чи молекули) можуть бути адсорбовані підкладкою та стати адатомами; 2) десорбція -адатоми з певною ймовірністю можуть десорбувати в газову фазу; 3) адатоми можуть взаємодіяти, утворюючи скупчення адатомів (структури); 4) адатоми можуть дифундувати вздовж підкладки [32][33][34][35][36][42][43][44]; 5) адатоми можуть формувати стійкі димери на під-кладці [39,40,45]. Такі процеси відповідають окремому випадку нерівноважних квазихемічних реакцій.…”
Section: модельunclassified
See 2 more Smart Citations